Money Buddy / Nurularina Muslim … [et al.] - Muslim, Nurularina; Rosli, Fasihah; Taupis, Irdina Hafizah; Zolkeplay, Aishah Izwani; Iskandar, Hanisah; Ismail, Aisyah; Ibrahim, Khalilah (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2024)
Financial literacy is crucial for individuals to make informed decisions and plan their finances. However, people with disabilities often face difficulties in accessing financial education resources that meet their needs independently. As a result of this, people with disabilities are often targeted in financial fraud as they lack knowledge. To address this gap, researchers have introduced an innovative mobile application powered by artificial intelligence (AI) that is specifically for people with disabilities which is “Money Buddy”. “Money Buddy” uses AI and natural language processing (NLP) technology to provide personalized financial advice. This app merely focuses on giving people with disabilities a financial education. The objective is to raise financial awareness, promote consumer resilience, and encourage financial independence. The app features tailored for people with disabilities, such as a voice-activated assistant, screen reader compatibility, adjustable text sizes, and voice narration. These unique features should be highlighted prominently as they set the app apart from generic financial education platforms. The benefit of this application is that it can provide the necessary knowledge and tools to assist users in making informed financial decisions on budgeting, saving, investing, and managing their debt. Other than that, it also provides comprehensive education on common scams and tactics used by scammers to help users stay updated. Therefore, using "Money Buddy", will help improve financial literacy among individuals with disabilities and have a great impact on society, leading to positive economic outcomes at the individual and community levels.